Azithromycin-chloroquine and the intermittent preventive treatment of malaria in pregnancy - Chico, R Matthew (BioMed Central, 2008)
In the high malaria-transmission settings of sub-Saharan Africa, malaria in pregnancy is an important cause of maternal, perinatal and neonatal morbidity. Intermittent preventive treatment of malaria in pregnancy (IPTp) with sulphadoxine-pyrimethamine (SP) reduces the incidence of low birth-weight, pre-term delivery, intrauterine growth-retardation and maternal anaemia. However, the public health benefits of IPTp are declining due to SP resistance. The combination of azithromycin and chloroquine is a potential alternative to SP for IPTp. This review summarizes key in vitro and in vivo evidence of azithromycin and chloroquine activity against Plasmodium falciparum and Plasmodium vivax, as well as the anticipated secondary benefits that may result from their combined use in IPTp, including the cure and prevention of many sexually transmitted diseases. Drug costs and the necessity for external financing are discussed along with a range of issues related to drug resistance and surveillance. Several scientific and programmatic questions of interest to policymakers and programme managers are also presented that would need to be addressed before azithromycin-chloroquine could be adopted for use in IPTp.